The Effect of a Scientific Approach Based on Problem Based Learning Models on Students Science Problem Solving Skills at Madrasah Ibtidaiyah - Jelita Jelita*; Nuraida Nuraida (Jurnal Pendidikan Sains Indonesia, 2023)
The ability to solve problems shows a persons ability to think critically by using the reasoning and knowledge they have. The purpose of this study was to determine the effect of a scientific approach based on problem based learning on students science problem solving skills at Madrasah Ibtidaiyah Negeri 2 Aceh Tamiang. This research is quantitative research with an experimental method. The population is all students of class V MIN 2 Aceh Tamiang, totaling 60 people and the sample used is VA class as the control class and VB class as the experimental class. Each class consists of 30 people. The research instrument was a test in the form of an essay totaling 3 questions of indicators of problem solving skills namely identifying problems, describing various strategies, solving problems, and solving problems systematically. From the results of the data analysis, the class average value was obtained. The experiment was higher than the control class with a difference of 54.67 and an increase of 63.87%. The findings from the hypothesis testing indicate a significance level of 5%. The calculated t-value 18.41 exceeds the critical t-value 2.41 for the shown degrees of freedom 18.41 or the two-tailed significance value 0.00 is less than 0.05. Consequently, the alternative hypothesis (Ha) is accepted. The conclusion is an effect of a scientific approach based on problem learning on students science problem solving skills at Madrasah Ibtidaiyah Negeri 2 Aceh Tamiang and this approach is good for learning science